Social pressure in decision making: Home advantage in Mexican football - Velázquez Guadarrama, César; Hernández Velázquez, Juan Martín (Estudios Económicos de El Colegio de México, 2024)
One of the explanations for the home advantage in football is the social pressure the public exerts on players and referees. In this context, this work aims to study the determinants of this fact in Mexican football. The results show that crowd support does not affect the advantage of playing at home. Referees do respond to social pressure by showing a higher number of yellow cards, but to both teams, which eliminates any bias in favor of the home team. These results are contrary to what has been found for Europe.